2018
DOI: 10.1212/wnl.0000000000005790
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial design for cutaneous neurofibromas

Abstract: Objective Several clinical trials targeting cutaneous neurofibromas (cNF) have been conducted; however, none has resulted in meaningful changes to care. The Clinical Trial Design and Development subgroup's goals were to (1) define key considerations in the design of clinical trials for cNF, (2) summarize existing data in relation to these considerations, and (3) provide consensus recommendations about key elements of trial design to accelerate the clinical development of therapies for cNF. MethodsThe subgroup,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In considering cNF from a therapies development standpoint, there are multiple factors to balance, including the goal of treatment, anatomic region, tumor depth and size, short-and long-term toxicity, and the route of administration. Likewise, considerations for clinical trial designs are essential (Cannon et al 6 ) For cNF, achieving the requisite balance is complicated not only by the challenges in effectively delivering drug into the deep dermis, but also the high safety margin required for a nonfatal tumor that may require long-term drug exposure. Based on this, a product will have to demonstrate clinically meaningful therapeutic benefit with acceptable safety, and justifiable cost of goods to spur investment in its Locations of cNF tumors, especially in places that are visible (e.g., face), are important to patients.…”
Section: Discussionmentioning
confidence: 99%
“…In considering cNF from a therapies development standpoint, there are multiple factors to balance, including the goal of treatment, anatomic region, tumor depth and size, short-and long-term toxicity, and the route of administration. Likewise, considerations for clinical trial designs are essential (Cannon et al 6 ) For cNF, achieving the requisite balance is complicated not only by the challenges in effectively delivering drug into the deep dermis, but also the high safety margin required for a nonfatal tumor that may require long-term drug exposure. Based on this, a product will have to demonstrate clinically meaningful therapeutic benefit with acceptable safety, and justifiable cost of goods to spur investment in its Locations of cNF tumors, especially in places that are visible (e.g., face), are important to patients.…”
Section: Discussionmentioning
confidence: 99%
“…One proposed classification system assigns 1 of 5 subcategories to describe the clinical appearance of cNF 28 : nascent, flat, sessile, globular, or pedunculated (figure 2). The nascent/latent cNF (figure 2A) is not apparent by inspection or palpation of the skin, but can be appreciated by proper imaging techniques, such as highresolution ultrasound (US) and optical coherence tomography (OCT) imaging, which are discussed by Cannon et al 29 in this series. The flat cNF (figure 2B) is visible at the skin surface, and is distinguished primarily by its slightly raised surface.…”
Section: Cutaneous Neurofibromas: Clinical Definitions or Descriptorsmentioning
confidence: 99%
“…The natural history of cNF is still poorly understood due to an extensive interpatient and intrapatient heterogeneity in cNF presentation, degree of severity and behavior over time described extensively in the literature [9]. Although these lesions are not life-threatening, they are known to dramatically affect the quality of life of patients due to the visibility of the lesions and stigmatization [1, 1012].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the major impact cNF has on patients’ quality of life, the medical need is huge. Unfortunately, there is no treatment approved to cure cNF, patients are currently offered surgical removal or physical destruction using laser or electrodessication [7, 9]. In parallel, notable therapeutic advances have been made for plexiform neurofibromas and recent clinical trials evaluating MEK inhibitors have shown promising results [13].…”
Section: Introductionmentioning
confidence: 99%